A Comprehensive Review of the Pear Fungal Diseases. Issue 4 (1st October 2016) - Sardella, Davide; Muscat, Arianne; Brincat, Jean-Pierre; Gatt, Ruben; Decelis, Stephen; Valdramidis, Vasilis
ABSTRACT: In this article a detailed review of the fungal diseases that can affect pear fruit is provided. Each section comprises a complete description of the fungi responsible for the diseases and the symptoms they produce on the pears. The majority of pear fungal diseases, including blue mold, grey mold, bitter rot, black spot, brown rot, bull's eye rot, Phytophthora rot, pink mold rot, powdery mildew, Rhizopus rot, scab, side rot, sooty blotch, and flyspeck, are presented. Sources of infection are comprehensively described in relation to harvesting or post-harvesting handling and intervention practices, respectively. As these diseases are dependent on a number of environmental parameters, the optimal temperature ranges for disease development are described and the causal agents are identified. Previous studies on the diagnostic indications are reviewed while information about the optimal environmental parameters of temperature, pressure, pH, water activity, and oxygen level for the fungal growth is comprehensively summarized.